Inflammatory Factors of the Tumor Microenvironment Induce Plasticity in Nontransformed Breast Epithelial Cells: EMT, Invasion, and Collapse of Normally Organized Breast Textures - Tal Leibovich-Rivkin (Neoplasia: An International Journal for Oncology Research, 2013)
Nontransformed breast epithelial cells that are adjacent to tumor cells are constantly exposed to tumor necrosis factor-α (TNFα) and interleukin-1β (IL-1β), two inflammatory cytokines identified as having pro-tumoral causative roles. We show that continuous stimulation of nontransformed breast epithelial cells by TNFα + IL-1β for 2 to 3 weeks induced their spreading and epithelial-to-mesenchymal transition (EMT). The mechanistic bases for this slow induction of EMT by TNFα + IL-1β are: 1) it took 2 to 3 weeks for the cytokines to induce the expression of the EMT activators Zeb1 and Snail; 2) although Twist has amplified the EMT-inducing activities of Zeb1 + Snail, its expression was reduced by TNFα + IL-1β; however, the lack of Twist was compensated by prolonged stimulation with TNFα + IL-1β that has potentiated the EMT-inducing activities of Zeb1 + Snail. Stimulation by TNFα + IL-1β has induced the following dissemination-related properties in the nontransformed cells: 1) up-regulation of functional matrix metalloproteinases; 2) induction of migratory and invasive capabilities; 3) disruption of the normal phenotype of organized three-dimensional acini structures typically formed only by nontransformed breast cells and spreading of nontransformed cells out of such acini. Our findings suggest that TNFα + IL-1β induce dissemination of nontransformed breast epithelial cells and their reseeding at the primary tumor site; if, then, such detached cells are exposed to transforming events, they may form secondary malignant focus and lead to disease recurrence. Thus, our study reveals novel pathways through which the inflammatory microenvironment may contribute to relapsed disease in breast cancer.